To find the nth term of a sequence, we first need to identify the pattern or rule governing the sequence. In this case, the sequence appears to be increasing by consecutive odd numbers: 10, 14, 18, 22, and so on. To find the nth term, we can use the formula for the nth term of an arithmetic sequence: a_n = a_1 + (n-1)d, where a_n is the nth term, a_1 is the first term, n is the position of the term, and d is the common difference. In this sequence, a_1 = 6 and the common difference is 10. Therefore, the nth term can be expressed as a_n = 6 + (n-1)10.
Oh, what a delightful sequence you have there! To find the nth term, we first need to identify the pattern. It looks like the differences between consecutive terms are increasing by 4 each time. So, the nth term can be calculated using the formula: nth term = 2n^2 + 2. Happy calculating, my friend!
It goes up by (24-16) = 8 each time. The first time is 16. So the nth term is 8n + 8.
Looks like 57: 12+9=21, +9=30, +9=39, +9=48, +9=57.
If 3 is the first term, then the nth term is [ 3 x 2(n-1) ] .
If 3 is the first term, then the nth term is [ 3 x 2(n-1) ] .
Sn = 3n2 + 2n - 8
It goes up by (24-16) = 8 each time. The first time is 16. So the nth term is 8n + 8.
Looks like 57: 12+9=21, +9=30, +9=39, +9=48, +9=57.
If you mean: 8 28 48 and 68 then the nth term is 20n -12 and so the next number will be 88
> since the value rises by nine at each step and the first term is 12 the formula for > the nth term is: 12+(n-1)*9 Which simplifies to Sn = 9n + 3
If 3 is the first term, then the nth term is [ 3 x 2(n-1) ] .
If 3 is the first term, then the nth term is [ 3 x 2(n-1) ] .
Sn = 3n2 + 2n - 8
48/30 = 16/10 = 1.6/1 = 1.6
Had it not been for 64, the nth term would be given by t(n) = 3*n2 However, this cannot be the case because then t(4) would have been 48, not 64.
t(n) = 3*2n-1 Or just 3*2n
1.6% of 48= 1.6% * 48= 0.016 * 48= 0.768
48 and 16/30